Lunar and Planetary Science Boosted by Citizen Science Projects. (2nd April 2013) - Kumar, Mohi
Abstract : From efforts to help scientists remotely monitor meteorites hitting the Moon to campaigns to count craters on raw images of the asteroid Vesta, creative strategies to utilize the public's ability to collect and analyze data are being employed for a variety of lunar and planetary science projects. According to speakers at a session called "Rising to the challenge: Improving public understanding of science in the next decade, " held at the 44th annual Lunar and Planetary Science Conference in The Woodlands, Tex., from 18 to 22 March, these citizen science projects tap into public enthusiasm about worlds beyond our own.